Otimização da torrefação na composição físico-química e fenólica, capacidade antioxidante e compostos voláteis do óleo de babaçu (Orbignya phalerata) - Souza, Iago Hudson da Silva (2020)
Babassu oil has its concentrations of bioactive compounds increased when the seeds are pre-treated by heat before the oil is extracted. The use of roasting can increase its commercial value, since bioactive compounds tend to pass into the oil according to the degree of roasting applied. The aim of the present study was to optimize the roasting of babassu seeds using the response surface methodology (MSR) and the Desirability function. A central rotational composite design (RCCD) was used to investigate the effects of two independent variables. Temperature (X1) and roasting time (X2) significantly affect response variables: yield (%), total phenolic content (TPC), number of phenolic compounds (NPC), ORAC, acidity and peroxide index. The quadratic model was adjusted for most responses. The roasting temperature of 222 °C and the roasting time of 43 min were standardized as ideal conditions. Thus, the oil in the optimized condition showed a yield of 54.47%, a content of phenolic compounds (TPC) of 91.53 mg GAE/100 g. However, in the control oil there was no presence of phenolic compounds analyzed by HPLC-DAD, whereas in the optimized conditions, 7 phenolic compounds were observed. The model of optimized conditions showed a good correlation between the predicted and experimental values. In general, these results demonstrate the effectiveness of roasting in improving the quantity of bioactive compounds in babassu oil.